1.Uprośc wyrażenia.

a) 6(a+2b) - 3 (2a - 3b)
b. 4(b+3)+3(a-b)
c. 7( b+c) - 3(b+2c)
d. 5(a+3)+ 2b - 3 (a+b)
e. 6(3+z)-4(2z+4)+2(8+z)
f. -4(2x - 7 - 3y) - 12(-y-x)
2. Przekształc wyrażenie na sumę i wykonaj redukcję wyrazów podobnych.
3(b-5a)-2(3b+a)
4(x/4 +y/4)-5(3x/5 - 7y/5)
-6(3x/6 - 2y/6) + 2/3(3x/2 - 6y)

3

Odpowiedzi

Najlepsza Odpowiedź!
  • Użytkownik Zadane
2010-03-20T17:18:08+01:00
1.
a. 6a+12b-6a+9b=21b
b. 4b+12+3a-3b=3a-b+12
c. 7b+7c-3b-6c=4b+c
d. 5a+15+2b-3a-3b=2a-b+15
e. 18+6z-8z-16+16+2z=18
f. -8x+28+12y+12y+12x=24y+4x+28

2.
3b-15a-6b-2a=-17a-3b

4(x/4 +y/4)-5(3x/5 - 7y/5) *20
80(x+y)-100(3x-7y)=80x+80y-300x+700y=-220x+780y

-6(3x/6 - 2y/6) + 2/3(3x/2 - 6y) *6
-36(3x-2y)+4(9x-36y)=-108x+72y+36x-144y=-72x-72y
1 1 1
  • Użytkownik Zadane
2010-03-20T17:26:15+01:00
1
a) 6(a+2b) - 3 (2a - 3b)=6a+12b-6a+9b=21b
b. 4(b+3)+3(a-b)=4b+12+3a-3b=3a+b+12
c. 7( b+c) - 3(b+2c)=7b+7c-3b-6c=4b+1c
d. 5(a+3)+ 2b - 3 (a+b)=5a+15+2b-3a-3b=2a-1b+15
e. 6(3+z)-4(2z+4)+2(8+z)=18+6z-8z-16+16+2z=18
f. -4(2x - 7 - 3y) - 12(-y-x)=-8x+14+12y+12y+12x=4x+24y+14
2.
a)3(b-5a)-2(3b+a)=3b-15a-6b-2a=-17a-3b
b)4(x/4 +y/4)-5(3x/5 - 7y/5)=4x/4+16/4-15x/5-3y/5=4x/4-15x/4-35y/54=20x/20-60x/20-35y/5+4=-40x/20-35y5+4=-2x-7y+4
c)-6(3x/6 - 2y/6) + 2/3(3x/2 - 6y)=-18x/6+12y/6+6x/6-12y/3=-3x+2y+x-4y=-2x-2y

1 1 1
2010-03-20T17:28:41+01:00
A) 6(a+2b) - 3 (2a - 3b)
6a+12b-6a+9b
21b

b. 4(b+3)+3(a-b)
4b+12+3a-3b
b+12+3a

c. 7( b+c) - 3(b+2c)
7b+7c-3b-6c
4b+c

d. 5(a+3)+ 2b - 3 (a+b)
5a+15+2b-3a-3b
2a+15-b

e. 6(3+z)-4(2z+4)+2(8+z)
18+6z-8z-16+16+2z
18

f. -4(2x - 7 - 3y) - 12(-y-x)
-8x+28+12y+12y+12x
4x+24y+28

2.
3(b-5a)-2(3b+a)
3b-15a-6b-2a
-3b-17a

4(x/4 +y/4)-5(3x/5 - 7y/5)
x+y-3x+7y
-2x+8y

-6(3x/6 - 2y/6) + 2/3(3x/2 - 6y)
-3x+2y+x-4y
-2y-2x
1 5 1